Evaluation of switch-mediated costimulation in trans on universal CAR-T cells (UniCAR) targeting CD123-positive AML. (1st January 2021) - Meyer, Jan-Erik; Loff, Simon; Dietrich, Josephine; Spehr, Johannes; Jurado Jiménez, Gabriel; von Bonin, Malte; Ehninger, Gerhard; Cartellieri, Marc; Ehninger, Armin
ABSTRACT: Chimeric antigen receptor T cells (CAR-T) targeting CD19 have achieved significant success in patients with B cell malignancies. To date, implementation of CAR-T in other indications remains challenging due to the lack of truly tumor-specific antigens as well as control of CAR-T activity in patients. CD123 is highly expressed in acute myeloid leukemia (AML) blasts including leukemia-initiating cells making it an attractive immunotherapeutic target. However, CD123 expression in normal hematopoietic progenitor cells and endothelia bears the risk of severe toxicities and may limit CAR-T applications lacking fine-tuned control mechanisms. Therefore, we recently developed a rapidly switchable universal CAR-T platform (UniCAR), in which CAR-T activity depends on the presence of a soluble adapter called targeting module (TM), and confirmed clinical proof-of-concept for targeting CD123 in AML with improved safety. As costimulation via 4–1BB ligand (4–1BBL) can enhance CAR-T expansion, persistence, and effector functions, a novel CD123-specific TM variant (TM123-4-1BBL) comprising trimeric single-chain 4–1BBL was developed for transient costimulation of UniCAR-T cells (UniCAR-T) at the leukemic site in trans . TM123-4-1BBL-directed UniCAR-T efficiently eradicated CD123-positive AML cells in vitro and in a CDX in vivo model. Moreover, additional costimulation via TM123-4-1BBL enabled enhanced expansion and persistence with a modulated UniCAR-T phenotype. In addition, the increased hydrodynamic volume of TM123-4-1BBL prolonged terminal plasma half-life and ensured a high total drug exposure in vivo . In conclusion, expanding the soluble adapter optionality for CD123-directed UniCAR-T maintains the platforms high anti-leukemic efficacy and immediate control mechanism for a flexible, safe, and individualized CAR-T therapy of AML patients.